Identifikasi Variasi Media Pembelajaran yang Digunakan Oleh Guru Biologi Di SMA Negeri 11 Pekanbaru - Tasya Bahira; Nurul Fauziah; Nurkhairo Hidayati (CV.ITTC INDONESIA, 2026)
This study aims to identify variations in learning media used by biology teachers at State Senior High School 11 Pekanbaru. The study used a qualitative descriptive design with two biology teachers as subjects. Data were collected through interviews and analyzed through data reduction, data presentation, and conclusion drawing. The results show that teachers consistently use media at every meeting, including technology-based and non-technology media. Technological media such as PowerPoint, videos, animations, digital modules, as well as the use of AI and QR code-based attendance are considered effective in increasing student engagement and understanding of abstract biology material. The main obstacle, namely network and power outages, was overcome by the use of alternative media. These findings indicate that a variety of learning media has been implemented to support the effectiveness of biology learning.